B cell-activating factor (BAFF) from dendritic cells, monocytes and neutrophils is required for B cell maturation and autoantibody production in SLE-like autoimmune disease - Giordano, Daniela; Kuley, Runa; Draves, Kevin E.; Elkon, Keith B.; Giltiay, Natalia V.; Clark, Edward A. (Frontiers in Immunology, 2023)
B cell-activating factor (BAFF) contributes to the pathogenesis of autoimmune diseases including systemic lupus erythematosus (SLE). Although several anti-BAFF Abs and derivatives have been developed for the treatment of SLE, the specific sources of BAFF that sustain autoantibody (auto-Ab) producing cells have not been definitively identified. Using BAFF-RFP reporter mice, we identified major changes in BAFF-producing cells in two mouse spontaneous lupus models (Tlr7 Tg mice and Sle1), and in a pristane-induced lupus (PIL) model. First, we confirmed that similar to their wildtype Tlr7 Tg and Sle1 mice counterparts, BAFF-RFP Tlr7 Tg mice and BAFF-RFP Sle1 mice had increased BAFF serum levels, which correlated with increases in plasma cells and auto-Ab production. Next, using the RFP reporter, we defined which cells had dysregulated BAFF production. BAFF-producing neutrophils (Nphs), monocytes (MOs), cDCs, T cells and B cells were all expanded in the spleens of BAFF-RFP Tlr7 Tg mice and BAFF-RFP Sle1 mice compared to controls. Furthermore, Ly6Chi inflammatory MOs and T cells had significantly increased BAFF expression per cell in both spontaneous lupus models, while CD8- DCs up-regulated BAFF expression only in the Tlr7 Tg mice. Similarly, pristane injection of BAFF-RFP mice induced increases in serum BAFF levels, auto-Abs, and the expansion of BAFF-producing Nphs, MOs, and DCs in both the spleen and peritoneal cavity. BAFF expression in MOs and DCs, in contrast to BAFF from Nphs, was required to maintain homeostatic and pristane-induced systemic BAFF levels and to sustain mature B cell pools in spleens and BMs. Although acting through different mechanisms, Nph, MO and DC sources of BAFF were each required for the development of auto-Abs in PIL mice. Our findings underscore the importance of considering the relative roles of specific myeloid BAFF sources and B cell niches when developing treatments for SLE and other BAFF-associated autoimmune diseases.